Deprivation of Liberty in the Shadows of the Institution - Series, Lucy (Bristol University Press, 2022)
ePDF and ePUB available Open Access under CC-BY-NC licence. During the 20th century the locus of care shifted from large institutions into the community. However, this shift was not always accompanied by liberation from restrictive practices. In 2014 a UK Supreme Court ruling on the meaning of 'deprivation of liberty' resulted in large numbers of older and disabled people in care homes, supported living and family homes being re-categorized as 'detained'. Placing this ruling in its social, historical and global context, this book presents a socio-legal analysis of social care detention in the post-carceral era. Drawing from disability rights law and the meanings of 'home' and 'institution' it proposes solutions to the Cheshire West ruling's paradoxical implications.